Components of ocean sea-level pressure and their relationship with rainfall over Southern Africa - Howes, Carolann (My University, 2015)
Monthly mean s e a - l e v e l p r e s s u r e ove r th e o c ea nic areas a d j a c e n t t o t h e Kepublic o f South A f r i c a i s an aly s e d . R ela t i o n s h i p s between t h e oceanic p r e s s u r e and r a i n f a l l over t h i s p a r t o f t h e c o n t i n e n t a re d i s c u s s e d . P r i n c i p a l compon e n ts a n a l y s i s is used t o d e r i v e u n c o r r e l a t e d f u n c t i o n s of th e o r i g i n a l p r e s s u r e v a r i a b l e s . Three major p r e s s u r e f i e l d s were i d e n t i f i e d , termed a g e n e r a l , a l o n g i t u d i n a l and a l a t i t u d i n a l p r e s s u r e f i e l d . The r e l a t i o n s h i p s between p r e s s u r e and r a i n f a l l a re a s s e s s e d by r e g r e s s i n g monthly r a i n f a l l on t h e p r i n c i p a l comnonent s c o r e s . R a i n f a l l in w in te r maxima a r e a s appears t o be d i r e c t l y r e l a t e d t o oceanic s e a - l e v e l p r e s s u r e s i t u a t i o n s , whereas the r e s t o f th e country shows an o u t - o f - s e a s o n r e l a t i o n s h i p between r a i n f a l l and p r e s s u r e over n o n - c o n t i n e n t a l a r e a s .
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, for the degree of Master of Science. Johannesburg, 1980
Keywords: Rainfall probabilities; Sea level; Atmospheric pressure